Effect of Using Asean Regional Capacity on Disaster Health Management (Arch Project)'S Health Needs Assessment Toolkit to Assess the Damage of Storm Linfa Affected in the Central Provinces of Vietnam in October 2020 - Tien Dung Nguyen; Nhu Lam Nguyen; Duc Chinh Nguyen; Thi Hanh Trang Do; Huy Minh Nguyen; Quoc Chieu Le; Quang Phu Tran; Thi Thu Trang Phan (ASEAN Journal of Disaster Health Management (AJDHM), 2025)
Introduction: A Health Needs Assessment (HNA) after a disaster is essential to inform health care planning and delivery. In 2018, the ARCH project developed the Standard Operating Procedures for disaster health management in ASEAN countries, which included the HNA toolkit. This study aims to assess the impacts of Storm Linfa in October 2020 in the central provinces of Vietnam and the applicability of the ARCH project's HNA toolkit. Methods: The ARCH project's HNA toolkit was used to assess the damage severity in 5 provinces in central Vietnam. The data was collected by secondary data, in-depth interviews, and direct observation at the scene by independent survey teams in two weeks, processed by Microsoft Excel and thematic analysis. Results: For the severity damages of the storm, a total of 710,076 people were affected by Storm Linfa with 20 missing and 72 deaths. Main sources of drinking water were bottled water (45.5%), piped water (25.6%), and rainwater, water stored in tanks (16.6%); 100% of households had unsafe sanitation and hygiene conditions; 100% of households lacked fresh food in the first two days; 100% of district hospitals were only partially functioning while the commune health stations had 20% functioning, five preventive medical centers had 3/5 (60%) partially functioning. For the applicability of HNA form, the ARCH project's HNA toolkit was helpful and easy to apply for the assessment of disaster damage and was feasible and covered all events at the scene. Conclusions: Storm Linfa caused serious damage to people and health care facilities in five provinces of the middle part of Vietnam. The ARCH project's HNA toolkit was helpful and comprehensive for the assessment of the severity of damage. It can be applied effectively with some modifications in real situations of natural disasters in Vietnam.